UV-cured anion-conducting polymer electrolyte membrane for quasi-solid-state zinc-air batteries

The cation-exchange polymer electrolyte membrane is synthesized through simple UV radiation treatment, which solves the corrosion problem of liquid electrolytes in zinc-air batteries, improves the conductivity and mechanical stability of the battery, and improves the safety and life of the battery.

JP2025504179APending Publication Date: 2025-02-06COUNCIL OF SCI & IND RES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024546442
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-07
Filing Date
2023-02-07
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

In existing zinc-air batteries, liquid electrolytes cause corrosion and degradation of battery performance. The traditional separator does not conduct electricity and increases dead weight, which affects the stability and safety of the battery.

Method used

The cation-exchange polymer electrolyte membrane was synthesized by simple UV radiation treatment. The crosslinked polymer electrolyte membrane was prepared by introducing quaternary ammonium salt groups into the polymer film, and a composite membrane was formed on glass fiber paper to improve conductivity and mechanical stability.

Benefits of technology

High conductivity, mechanical stability and safety improvements are achieved, reducing the dead weight of the battery, extending battery life and reducing the risk of corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504179000001_ABST
    Figure 2025504179000001_ABST
Patent Text Reader

Abstract

The present invention relates to anion exchange polymer electrolyte membranes (AEPEMs) using simple acrylate / methacrylate monomers / oligomers by a simple UV irradiation method, where at least one of the monomers / oligomers has a quaternary ammonium group to obtain a polymer membrane, and when immersed in a 6M KOH solution, OH groups are formed in the polymer matrix. - Groups have been introduced to obtain AEPEM with good ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of polymer electrolyte membranes for air-zinc batteries. More specifically, the present invention relates to a method for synthesizing anion-exchange polymer electrolyte membranes by a simple UV irradiation treatment. [Background technology]

[0002] Traditionally, the separator in zinc-air batteries (ZABs) is a porous polymer membrane (e.g., polypropylene) wetted with a liquid electrolyte, such as a 6M KOH aqueous solution. Similarly, glass fiber paper is often employed as a separator for ZAB applications. The role of these polymer membranes / glass fiber papers is to physically separate the negative and positive compartments so that they do not contact each other, but in many cases they are deadweight because they do not contribute to ionic conduction. Furthermore, the direct use of high pH liquid electrolytes, such as 6M KOH solutions, in ZABs accelerates the corrosion of the zinc anode, causes dendritic growth of zinc, and creates other safety concerns such as the risk of electrolyte leakage, which ultimately leads to reduced cycle stability leading to battery failure. Furthermore, KOH reacts with CO2 to produce carbonate precipitation, which leads to a decrease in electrolyte concentration. Furthermore, the carbonates block the pores, further reducing the battery performance. Also, water leakage from the electrolyte and oxygen bubbles accompanying the reaction reduce the battery performance.

[0003] To address these issues and improve the perspective of flexibility in ZABs, the choice of anion-exchange polymer electrolyte membranes (AEPEMs) is obvious. Compared to liquid electrolytes with ionic conduction for both cations and anions, AEPEMs have OH - Can assist in selective conduction of ions. Liquid electrolyte / OH -AEPEM, a mechanically stable and self-supporting polymer membrane with ion-containing groups, can improve flexibility and safety prospects when used in ZABs. Moreover, unlike neutral polymer separators / glass fiber separators, AEPEM's charged polymer host inherently contributes to ion conduction, minimizing the deadweight that results from other non-ion-conducting separators.

[0004] Traditionally, the preparation of AEPEM has been carried out by a laborious, top-down approach involving multiple synthetic steps.

[0005] Yang et al., Journal ofMembrane Science, 2014, 467, 48-55, prepared an AEPEM based on imidazolium salt. In this membrane preparation, a polymer host, poly(arylene ether sulfone) containing pendent imidazolium groups, was synthesized from 2-ethyl-4-methylimidazole through a multi-step process, which was then treated with n-bromobutane in dimethylacetamide and cast to obtain a polymer membrane. The resulting membrane was treated with 1M NaOH aqueous solution for 48 hours to obtain the OH group. - Converted to form, approximately 14 mScm -1 We obtained an AEPEM showing an ionic conductivity of

[0006] Wei et al., ACS Applied Materials & Interfaces, 2018, 10, 29593-29598, reported that chitosan (CS) and 24 mScm were synthesized by a simple polymer blending method. -1 By crosslinking the poly(diallyldimethylammonium chloride) (PDDA) composite with ionic conductivity of OH - A conductive AEMs film was developed.

[0007] In Fu et al., Energy &Environmental Science, 2016, 9, 663-670, an anion-conducting polymer electrolyte membrane was prepared based on functionalized cellulose nanofibers. In this paper, cellulose was extracted from softwood kraft pulp and then functionalized with quaternary ammonium groups to obtain an anion-conducting polymer electrolyte membrane with a conductivity of about 21.2 mScm. -1 A membrane with an ionic conductivity of .

[0008] Zhang et al., AdvancedEnergy Materials, 2016, 6, 1600476, developed a hydroxide ion conducting polymer electrolyte membrane with a layered structure based on functionalized graphene oxide and nanocellulose, and achieved a hydroxide ion conductivity of about 39 mScm. -1 The preparation of this composite electrolyte required a tedious multi-step process, including the synthesis of GO, extraction of nanocellulose, and subsequent functionalization with quaternary ammonium groups.

[0009] Lin et al., ChemSusChem,2018, 11, 3215-3224, achieved a 46.8mScm by a laborious blending method. -1 By introducing quaternary ammonium groups, which have high ionic conductivity, polyvinyl alcohol-based anion-conducting polymer electrolyte membranes were prepared. However, the method presented here is tedious and requires multiple synthesis steps.

[0010] In view of the above, the present inventors have proposed a novel and economical method for synthesizing an anion exchange polymer electrolyte membrane (AEPEM). Summary of the Invention [Problem to be solved by the invention]

[0011] An important object of the present invention is to provide a polymer electrolyte membrane for a quasi-solid-state zinc-air battery (ZAB).

[0012] Another object of the present invention is to provide a method for preparing a polymer electrolyte membrane for a quasi-solid-state zinc-air battery.

[0013] It is yet another object of the present invention to provide an economical method for the synthesis of anion exchange polymer electrolyte membranes (AEPEM).

[0014] Yet another object of the present invention is to introduce the concept of in-situ polymerization to strengthen the interface between the electrode and electrolyte in quasi-solid-state zinc-air batteries. [Means for solving the problem]

[0015] In one aspect, the present invention provides a simple and economical method for synthesizing anion exchange polymer electrolyte membranes (AEPEMs) from polymeric membranes referred to as AHMs.

[0016] The present invention further provides an anion exchange polymer electrolyte membrane (AEPEM) synthesized by the method of the present invention, and a battery comprising said membrane.

[0017] In one embodiment, the present invention relates to a method for preparing anion exchange polymer electrolyte membranes AEPEM and AEPEM-GF, the method comprising the steps of: a) preparing a reaction solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) adding 2-hydroxy-2-methylpropiophenone as a photopolymerization initiator or a free radical polymerization initiator to the reaction solution of step a); c) optionally immersing glass fiber paper (GF) in the reaction solution of step b); d) pouring the reaction solution of step b) or placing the GF soaked in the reaction solution of step c) between two polyethylene terephthalate films; e) subjecting said film to UV curing to obtain a cationic (or positively charged) polymer membrane (AHM) or a cationic (or positively charged) glass fiber polymer membrane (AHM-GF); and f) Treat the polymer membrane of step e) with a KOH solution to form OH - Doped anion exchange polymer electrolyte membrane (AEPEM) or OH - Forming a doped glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF), Here, at least one of the monomers has a quaternary ammonium salt (see Figures 1 to 4 and 9).

[0018] In yet another embodiment, all steps a)-f), including optional step c), are carried out at a temperature range of 20-30° C. without the need for a solvent.

[0019] In another aspect, the present invention relates to a battery having the anion exchange polymer electrolyte membrane disclosed herein.

[0020] In another aspect, the present invention relates to a zinc-air battery having: i Pt / C-RuO2 or Pt / C air cathode, or in-situ polymerized Pt / C-RuO2 or Pt / C air cathode; ii anion exchange polymer electrolyte membrane (AEPEM) or glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF); iii. a zinc anode, and iv. Metal case (see Figure 1 or 4).

[0021] In yet another embodiment, the metal case of the battery includes a base, spacer, and spring and is in the shape of a coin cell.

[0022] In yet another embodiment, the battery membrane exhibited stretchability up to 68-70% and tensile stress in the range of about 280-290 kPa (see FIG. 16).

[0023] In another aspect, the present invention provides an in-situ polymerized Pt / C or Pt / C-RuO2 air cathode for improving electrode-electrolyte contact in a quasi-solid-state zinc-air battery, the cathode being produced by a method comprising the steps of: a) brush-coating a reaction solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) subjecting the polymer-coated air cathode to UV polymerization to obtain an AHM coating on the cathode surface; and c) During device fabrication, the AHM polymer film is converted to an AEPEM film by contacting the AHM polymer film with a KOH solution of AEPEM or AEPEM-GF film (see Figures 4 and 9).

[0024] In yet another embodiment, the combination of AEPEM-GF composite electrolyte membrane with in-situ polymerized Pt / C or Pt / C-RuO2 air cathode improves the electrode-electrolyte contact in quasi-solid-state zinc-air batteries.

[0025] In another aspect, the present invention further comprises: a) an anode made of thin zinc foil with a thickness of 0.1 mm; b) a cathode having a Pt / C-RuO2 coated carbon cloth with a thin layer of polymer coating polymerized in-situ from a precursor solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; and c) AEPEM or AEPEM-GF membrane as quasi-solid electrolyte having The AEPEM or AEPEM-GF membrane is sandwiched between the modified carbon cloth and zinc foil to provide a flexible, rechargeable zinc-air battery (see Figures 1-4, 9, 19, and 20).

[0026] In another embodiment, the reaction solution comprises 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and poly(ethylene glycol) diacrylate (PEGDA).

[0027] In yet another embodiment, the reaction solution comprises 1-1.8 wt % 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), 4-7.2 wt % hydroxyethyl methacrylate (HEMA), 1-5 wt % poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and 1 wt % poly(ethylene glycol) diacrylate (PEGDA).

[0028] In yet another embodiment, the reaction solution comprises 1.2-1.6 wt % 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), 5.4-5.8 wt % hydroxyethyl methacrylate (HEMA), 2.8-3.2 wt % poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and 1 wt % poly(ethylene glycol) diacrylate (PEGDA).

[0029] In yet another embodiment, the monomer / oligomer disclosed in step a) is selected from poly(ethylene glycol) based monomers or oligomers, preferably the monomer / polymer is a poly(ethylene glycol) based derivative.

[0030] In certain embodiments, the present invention relates to a battery comprising an anion exchange polymer electrolyte membrane (AEPEM). [Brief description of the drawings]

[0031] [Figure 1] 1 is a schematic diagram illustrating the method of the present invention. [Diagram 2] 1 is a photograph of an AEPEM membrane produced by the method of the present invention. [Diagram 3] FIG. 1 is a schematic diagram of an AEPEM. [Figure 4] FIG. 1 is a schematic diagram of an air-zinc battery using the AEPEM produced by the method of the present invention. [Diagram 5] 1 is a plot of ionic conductivity versus temperature for AEPEM membranes based on AHM70:30, AHM50:50, and AHM90:10. [Figure 6] 1 shows the swelling test of polymer membranes of AHM 50:50, AHM 70:30 and AHM 90:10. [Figure 7] The electrolyte retention test of the AHM70:30 polymer membrane and a commercially available product is shown. [Figure 8] 1 shows a plot of stress versus strain for an AEPEM based on AHM70:30 membrane. [Figure 9] Schematic showing (a) in situ polymerization treatment on an air cathode and (b) comparison of the electrode-electrolyte interface in a quasi-solid-state zinc-air battery (ZAB) with and without in situ polymerization. [Figure 10] FIG. 1 is a schematic diagram of an AEPEM-GF membrane. [Figure 11] 1 shows a plot of specific capacity for Pt / C air cathode based ZAB with AEPEM membrane with (AEPEM ZAB with in-situ) and without (AEPEM ZAB without in-situ) in-situ polymerization method. [Figure 12] Electrochemical impedance spectroscopy (EIS) plots of Pt / C air cathode based ZAB with AEPEM membrane are compared with (AEPEM ZAB with in-situ) and without (AEPEM ZAB without in-situ) in-situ polymerization method. [Figure 13]1 shows a plot of specific capacity for AEPEM-GF composite electrolyte membrane-based ZAB with (AEPEM-GF ZAB with in-situ) and without (AEPEM-GF ZAB without in-situ) in-situ polymerization method. [Figure 14] Comparison of EIS data for AEPEM ZAB with in situ polymerization and AEPEM-GF ZAB without in situ polymerization. [Figure 15] 1 shows a plot of ionic conductivity versus temperature for the AEPEM-GF composite electrolyte membrane. [Figure 16] 1 is a plot of stress versus strain for the AEPEM-GF membrane. [Figure 17] Polarization plots of non-in-situ treated and in-situ treated rechargeable zinc-air batteries (rZABs) using state-of-the-art Pt / C-RuO2 catalyst coated gas diffusion layer (GDL) substrates as air cathodes. [Figure 18] The long-term charge-discharge plots of a zinc-air battery (rZAB) with (rZAB with in-situ) and without (rZAB without in-situ) in-situ treatment are shown using the state-of-the-art Pt / C-RuO2 catalyst coated GDL substrate as an air cathode. [Figure 19] 1 shows the polarization plot of the flexible rechargeable ZAB (F-rZAB) system. [Figure 20] This is a long-term charge / discharge plot of F-rZAB. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] As used herein, AHM refers to A=AOETMA, H=HEMA, and M=PEGMEMA.

[0033] This paper describes a method to prepare anion exchange polymer electrolyte membranes (AEPEMs) from simple acrylate / methacrylate monomers / oligomers via a simple UV irradiation process to obtain cross-linked polymers, which can be immersed in 6 M KOH aqueous solution to obtain polymer electrolytes that can replace the liquid electrolyte in rechargeable zinc-air batteries (ZABs).

[0034] Therefore, the method of the present invention uses a monomer containing a quaternary ammonium salt that undergoes free radical polymerization with an acrylate / methacrylate monomer / oligomer in one step to obtain a crosslinked polymer containing positively charged functional sites (anion exchange sites). The prepared positively charged polymer membrane can be immersed in a 6M KOH aqueous solution to obtain OH groups. - At 30°C, it can absorb approximately 32.5 mScm -1 Ionic conductivity of OH - The prepared membranes were found to have high mechanical and chemical stability both in the KOH swollen and unswollen state. The membranes of the present invention also exhibit air stability and can be stored under ambient conditions.

[0035] In one embodiment, the present invention relates to a method for preparing an anion exchange polymer electrolyte membrane (AEPEM), comprising the steps of: a) preparing a reaction solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) adding 2-hydroxy-2-methylpropiophenone as a photoinitiator or a free radical polymerization initiator to the reaction solution of step a); c) optionally, immersing glass fiber paper (GF) in the reaction solution of step b); d) pouring the reaction solution of step b) or placing the GF immersed in the reaction solution of step c) between two polyethylene terephthalate films; e) subjecting said film to UV curing to obtain a cationic (or positively charged) polymer membrane (AHM) or a cationic (or positively charged) glass fiber polymer membrane (AHM-GF); and f) Treat the polymer membrane of step e) with a KOH solution to form OH - Doped anion exchange polymer electrolyte membrane (AEPEM) or OH - Forming a doped glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF), Here, at least one of the monomers has a quaternary ammonium salt (see FIGS. 1 to 4 and 9).

[0036] In another embodiment, all steps a) to f), including optional step c), are carried out at a temperature range of 20-30° C. without the need for a solvent.

[0037] In another embodiment, the method of the present invention uses a reaction solution (also called precursor solution) containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA) (1-1.8 wt%), hydroxyethyl methacrylate (HEMA) (4-7.2 wt%), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA) (5-1 wt%), and poly(ethylene glycol) diacrylate (PEGDA) (1 wt%) as monomers / oligomers, which contribute to the mechanical stability of the electrolyte membrane upon UV curing. 2-Hydroxy-2-methylpropiophenone (HMPP) (or 1-hydroxy-cyclohexyl phenyl ketone) (1 wt%) is used as a photoinitiator. Approximately 0.5 mL of the liquid reactive mixture with the desired ratio (50:50, 70:30, 90:10) was poured between two polyethylene terephthalate (PET) films and UV cured for 15-20 min, resulting in cross-linking polymerization and a polymer electrolyte membrane with solid-like operability and dimensional stability. Stable membranes of various compositions were obtained by varying the monomer concentration and fixing the composition of cross-linker and initiator at 1 wt%. The membranes thus formed were treated with 6 M KOH aqueous solution for 24-28 h to obtain the OH-polymer. -A polymer membrane doped with cations is formed and called an anion exchange polymer electrolyte membrane (AEPEM).

[0038] In another embodiment, the present invention provides a method for preparing a glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF), the method comprising the steps of: a) preparing a reaction solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) adding 2-hydroxy-2-methylpropiophenone as a photoinitiator or a free radical polymerization initiator to the reaction solution of step a); c) Immersing glass fiber paper (GF) in the reaction solution of step b); d) pouring the reaction solution of step b) or placing the GF soaked in the reaction solution of step c) between two polyethylene terephthalate films; e) subjecting the film to UV curing to obtain a cationic (or positively charged) polymer electrolyte membrane (AHM) or a cationic (or positively charged) glass fiber polymer electrolyte membrane (AHM-GF); and f) The polymer electrolyte membrane of step e) is treated with a KOH solution, and OH - forming a doped glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF); Here, at least one of the monomers has a quaternary ammonium salt (see FIGS. 1 to 4 and 9).

[0039] The preparation method of the reaction solution (AHM 70:30) has the following steps: Take 1.4wt% AOETMA into a vial, Add 5.6 wt% HEMA to the above solution at room temperature and shake on a vortex stirrer for 3 to 5 minutes. Add 3 wt% PEGMEMA to the above mixture and shake for 3 to 5 minutes. Add 1wt% PEGDA to the above solution and mix well. Finally, 1 wt% of HMPP initiator is added to the above solution before UV polymerization.

[0040] To prepare AHM70:30, about 500 μL of the reaction solution was poured between two PET films and UV cured for 15 minutes to obtain a polymer electrolyte membrane through cross-linking polymerization. To obtain an anion-exchange polymer electrolyte membrane, the obtained membrane was immersed in 6M KOH for about 24 hours and then OH was added to the PET film. - Convert to a conductivity type.

[0041] Similarly, AHM 50:50 and AHM 90:10 membranes were prepared with the compositions shown in Table 1.

[0042] In another embodiment, the present invention relates to a battery comprising the anion exchange polymer electrolyte membrane disclosed herein.

[0043] In another embodiment, the present invention provides v Pt / C or Pt / C-RuO2 air cathode or in-situ polymerized Pt / C or Pt / C-RuO2 air cathode; TIFF2025504179000002.tif30156 vi Anion exchange polymer electrolyte membrane (AEPEM) or glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF); vii. Zinc anodes, and viii Metal casing The present invention relates to a zinc-air battery having the above structure (see FIG. 1 or FIG. 4).

[0044] In yet another embodiment, the metal case of the battery includes a base, spacer, and spring and is in the shape of a coin cell.

[0045] In yet another embodiment, the cell membrane exhibited stretchability up to 68-70% and tensile stress of about 280-290 kPa (see FIG. 16).

[0046] In another embodiment, the present invention provides an in-situ polymerized Pt / C or Pt / C-RuO2 air cathode made by a process comprising: a) brush-coating a reaction solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) subjecting the polymer-coated air cathode to UV polymerization to obtain an AHM coating on the cathode surface; and c) The device is fabricated while the polymer coating is in contact with the AEPEM-GF membrane in KOH solution, after which the AHM coating becomes AEPEM-coated or AEPEM-GF-coated (see Figures 4 and 9).

[0047] In yet another embodiment, the combination of the AEPEM-GF composite electrolyte membrane with an in-situ polymerized Pt / C or Pt / C-RuO2 air cathode improves the electrode-electrolyte contact in zinc-air batteries.

[0048] In another embodiment, the present invention further provides a zinc-air battery having: d) Anode made of thin zinc foil with a thickness of 0.1 mm; e) a cathode having a Pt / C-RuO2 coated carbon cloth with a thin layer of polymer coating polymerized in-situ from a precursor solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; and f) AEPEM or AEPEM-GF membranes as quasi-solid electrolytes; Here, the AEPEM or AEPEM-GF membrane is sandwiched between modified carbon cloth and zinc foil (see Figs. 1–4, 9, 19, and 20).

[0049] In yet another embodiment, the reaction solution comprises 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and poly(ethylene glycol) diacrylate (PEGDA).

[0050] In yet another embodiment, the reaction solution comprises 1-1.8 wt % 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), 4-7.2 wt % hydroxyethyl methacrylate (HEMA), 1-5 wt % poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and 1 wt % poly(ethylene glycol) diacrylate (PEGDA).

[0051] In yet another embodiment, the reaction solution comprises 1.2-1.6 wt % 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), 5.4-5.8 wt % hydroxyethyl methacrylate (HEMA), 2.8-3.2 wt % poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and 1 wt % poly(ethylene glycol) diacrylate (PEGDA).

[0052] In yet another embodiment, the monomer / oligomer disclosed in step a) is selected from poly(ethylene glycol) based monomers or oligomers, preferably the monomer / polymer is a poly(ethylene glycol) based derivative.

[0053] In yet another embodiment, the present invention provides a method for producing (i) in-situ polymerized Pt / C or Pt / C-RuO2 air cathode; (ii) anion exchange polymer electrolyte membrane (AEPEM); (iii) a zinc anode, and (iv) Metal case The present invention provides an in-situ polymerized zinc-air battery comprising:

[0054] In yet another embodiment, the present invention provides a method for producing (i) in-situ polymerized Pt / C or Pt / C-RuO2 air cathode; (ii) glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF); (iii) a zinc anode, and (iv) Metal case The present invention provides an in-situ polymerization secondary battery comprising:

[0055] In yet another embodiment, the present invention provides a method for producing (i) in-situ polymerized Pt / C-RuO2 air cathode; (ii) glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF); (iii) a zinc anode, and (iv) Metal case The present invention provides an in-situ polymerized flexible zinc-air secondary battery comprising:

[0056] The membranes formed by the method of the present invention were further subjected to electrical conductivity and swelling tests. Additionally, the membranes were subjected to mechanical strength and electrolyte retention tests.

[0057] In another embodiment, the present invention further provides a method for preparing an AEPEM-GF composite membrane. Accordingly, the method includes immersing a glass fiber paper in a reaction solution, followed by free radical polymerization by UV irradiation. The prepared AEPEM / glass fiber (AEPEM-GF) composite is further immersed in a 6M KOH solution to obtain an AEPEM-GF composite electrolyte membrane.

[0058] Therefore, to prepare the AEPEM-GF composite electrolyte membrane, a small circular piece of glass fiber paper with a radius of 0.65 cm was immersed in the reaction solution (1 μL) so that the polymer precursor entered between the fibers of the glass fiber paper. The soaked glass fiber paper was then irradiated with UV for 15-20 min to obtain a dried chloride composite membrane. This dried membrane was then immersed in a 6 M KOH aqueous solution for 24-28 h to obtain an AEPEM-GF composite electrolyte membrane with OH groups (-) doped in the matrix.

[0059] Furthermore, through-plane conductivity tests of the AEPEM-GF composite electrolyte membrane were performed at different temperatures. The conductivity of the prepared samples was measured using EIS with the same procedure as for the AEPEM membrane. The conductivity measurements were performed at 10°C intervals between 20°C and 60°C. The temperature was controlled using an environmental test chamber. The conductivity of the composite membrane at 30°C was 9.0×10 -2 Scm -1 It was observed that the AEPEM-GF composite electrolyte membrane could be used as an anion-conducting quasi-solid electrolyte for the fabrication of flexible ZAB. The significance of the in-situ polymerization technique in improving the electrode-electrolyte interfacial contact of ZAB was also demonstrated.

[0060] In one embodiment, the in-situ polymerization method comprises the steps of: a) Take approximately 10 μL of the prepared AHM 70:30 reaction solution. b Pt / C or Pt / C-RuO2 air cathode was brush-coated with the above solution to obtain a uniform coating, followed by UV polymerization to obtain the AHM coating; and c) The above coated Pt / C or Pt / C-RuO2 air cathode is contacted with alkaline 6M KOH to obtain an AHM film on the cathode surface, which is transformed into an AEPEM ion film when contacted with alkaline 6M KOH electrolyte.

[0061] The combination of the AEPEM-GF composite electrolyte membrane prepared according to the above embodiment and the in-situ polymerization technique leads to better contact at the three-phase interface, which results in the plateau feature being restored in the discharge plot (Figure 13). Furthermore, when the AEPEM-GF composite membrane is used, the specific capacity of AEPEM-GF ZAB with in-situ is improved to 483mAh / g compared with that of AEPEM ZAB without in-situ (483mAh / g).

[0062] In a further embodiment of the present invention, a secondary zinc-air battery (rZAB) using the developed AEPEM-GF polymer electrolyte membrane was demonstrated using Pt / C-RuO2 catalyst-coated GDL or carbon cloth substrate as the air cathode with and without the in-situ polymerization technique. The system with the in-situ polymerized cathode (rZAB with in-situ) achieved a current density of 248 mA cm -2 140mWcm -1 The zinc-air battery without the in-situ polymerized cathode (rZAB) showed an excellent peak power density of 190 mA cm -2 120mWcm -2 The in-situ rZAB also showed a long-term charge / discharge of 28 hours without a significant increase in overpotential (Figures 17 and 18).

[0063] In another embodiment of the invention, a 2×4 cm 2 A large area flexible zinc-air battery (F-rZAB) system was fabricated and demonstrated. A thin zinc foil with a thickness of 0.1 mm was used as the anode. A thin layer of in-situ polymerized ionic coating catalyst coated on carbon cloth was used as the air cathode. The prepared AEPEM-GF membrane was sandwiched between the polymer-coated carbon cloth and zinc foil to form a flexible and rechargeable zinc-air battery (F-rZAB). The system exhibited an open circuit voltage (OCV) of approximately 1.35 V. Furthermore, linear sweep voltammetry (LSV) plots showed that the battery had a maximum output of 29 mW cm. -2The peak power density was 1.0 mA / cm2 (Figure 19). -2 The system was subjected to long-term charging and discharging and operated for 14 hours without any significant increase in overvoltage (Figure 20).

[0064] Furthermore, EIS analysis was performed to monitor the effect of using AEPEM-GF composite electrolyte membrane instead of plain AEPEM membrane.The EIS results clearly show that the use of AEPEM-GF composite electrolyte membrane together with in-situ technique (AEPEM-GF ZAB with in-situ) improves the interfacial contact, which is evident from the equivalent series resistance (ESR) as well as the charge transfer resistance value shifting further to the left (Figure 14).

[0065] In summary, the present invention relates to an anion-conducting polymer electrolyte membrane prepared by a UV-curing method for a quasi-solid-state air-zinc secondary battery. In the present invention, the inventors have developed a high ionic conductivity (9.0×10) polymer electrolyte membrane for use as a solid electrolyte in an air-zinc secondary battery. -2 Scm -1 ), a polymer-based electrolyte reinforced with glass fiber paper was fabricated, which exhibited high electrolyte uptake and retention properties as well as improved mechanical strength. The use of glass fiber paper creates voids in the polymer matrix, facilitating electrolyte uptake. Furthermore, in-situ polymerization of the precursor solution on the air cathode was employed to enhance the contact at the three-phase interface, which is usually compromised during the transition from liquid to solid / quasi-solid electrolyte. Furthermore, a quasi-solid-state zinc-air battery using the prepared AEPEM-GF polymer electrolyte was analyzed. Finally, a flexible quasi-solid-state zinc-air battery system was fabricated by combining the prepared polymer electrolyte membrane with the in-situ polymerization method, and its performance was demonstrated.

[0066] In general, the present invention provides a method for producing a OH - This paper relates to the fabrication of air-zinc batteries by combining a method for preparing ion-conducting polymer electrolyte membranes with light-induced free radical polymerization for strengthening the electrode-electrolyte interface. EXAMPLES

[0067] Example 1: Conductivity Test The through-thickness conductivity of AEPEM films prepared from the precursor solutions in Table 1 with different compositions was measured at different temperatures. The conductivity of the prepared samples can be measured by electrochemical impedance spectroscopy (EIS). The conductivity cells were fabricated as CR2032 coin cells by sandwiching the desired film with a radius of 0.65 cm and a thickness of about 0.045 cm between two stainless steel plates with a thickness of 1 mm. The conductivity measurements were performed at 10°C intervals between 20°C and 60°C. The temperature was controlled using an environmental test chamber.

[0068] The In(σ) versus temperature plot is shown in Figure 5. At 30°C, the conductivity of AEPEM in AHM90:10 is 8.5×10 -2 Scm -1 whereas the conductivities of AHM70:30 and AHM50:50 are 3.25×10 -2 Scm -1 , 9.87×10 -3 Scm -1 It was.

[0069] Furthermore, the AEPEM-GF composite membrane exhibited a 9.0 × 10 -2 Scm -1 This shows excellent ionic conductivity.

[0070] Example 2: Swelling test The polymer films prepared from the investigated AHM precursor solutions (Table 1) were dried and then cooled. - The solvent absorption of the AHM-free (sometimes called AHM polymer membrane) and AEPEM-GF dry membranes was measured by gravimetric method. In this method, the as-prepared dry polymer membrane (AHM polymer membrane) was immersed in 6 M KOH aqueous solution and weighed at 2-h intervals for 24 h. The solvent absorption of the AHM polymer membrane was calculated according to Equation 1: Solvent absorption % = (Wwet - Wdry / Wdry) × 100 Equation 1 Wwet and Wdry are the wet and dry weights of the polymer membrane. The average solvent uptake was determined as the average of two samples to reduce error.

[0071] From Figure 6, it can be seen that the polymeric membranes based on AHM90:10 have better solvent adsorption than the other membranes. However, the mechanical stability of these AHM90:10 membranes is lost after swelling in 6 M KOH solution for 24 h. This loss of mechanical stability offsets the advantages of AHM90:10 due to its better electrical conductivity and solvent absorption. Therefore, further research was carried out on AHM70:30, which has improved mechanical stability and also has a fairly good ionic conductivity, as a possible better alternative to aqueous electrolytes. The AEPEM-GF composite membranes showed improved electrolyte absorption compared to all other AHM membranes.

[0072] Example 3: Electrolyte Retention Test Electrolyte retention tests of AEPEM and AEPEM-GF membranes based on AHM70:30 were performed gravimetrically at 25°C, with weights measured at 2-hour intervals over a 24-hour period, and compared with a conventional commercial membrane treated with 6M KOH solution. Figure 7 shows that the AHM70:30 polymer membrane has better water retention than the commercial membrane, which dries out completely after 2 hours.

[0073] Example 4: Mechanical Strength Test Tensile strength tests of the optimized AEPEM based on the AHM70:30 precursor solution were further carried out (Figure 8). According to the obtained stress-strain plot, the prepared membrane exhibited fairly good stretchability up to 23-28% and had a tensile stress of about 60-65 kPa, whereas the AEPEM-GF membrane exhibited excellent stretchability up to 68-70% and had a tensile stress of about 280-290 kPa (see Figure 16). Therefore, from the above data, it can be concluded that the prepared membrane has a reasonable mechanical stability even under high stress.

[0074] Example 5: Manufacturing Method A reaction solution (also called precursor solution) consisting of 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), polyethylene glycol methyl ether methacrylate (PEGMEMA) and polyethylene glycol diacrylate (PEGDA) was prepared as monomers, which contribute to a mechanically stable polymer electrolyte membrane upon UV curing. In addition, 2-hydroxy-2-methylpropiophenone (HMPP) was used as a photopolymerization initiator and added to the reaction solution in a desired ratio, and then poured between two Mylar films and UV cured for 15 minutes to crosslink and polymerize the solution, obtaining a polymer electrolyte membrane with solid-like operability and dimensional stability. By changing the concentration of the monomer and fixing the composition of the crosslinker and initiator at 1 wt%, stable membranes of various compositions were obtained. The membranes thus obtained were prepared by mixing the chloride form (Cl - ) and dry. For use in zinc-air batteries, the membrane was treated with 6M KOH in water for 24 hours and then cooled to 50°C. - It needs to be converted into a form.

[0075] Advantages of the Invention The method for preparing the membrane is simple. · Raw materials are easily available. The polymer matrix itself contributes to ionic conductivity through quaternary ammonium groups. Improved electrode-electrolyte contact through in-situ polymerization.

Claims

1. 1. A method for preparing an anion exchange polymer electrolyte membrane, comprising: a) preparing a reaction solution comprising 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) adding 2-hydroxy-2-methylpropiophenone as a photopolymerization initiator or a free radical polymerization initiator to the reaction solution of step a); c) optionally immersing a glass fiber paper (GF) in the reaction solution of step b); d) pouring the reaction solution of step b) or placing the GF immersed in the reaction solution of step c) between two polyethylene terephthalate films; e) subjecting the film of step d) to UV curing to obtain a cationic (or positively charged) polymer membrane (AHM) or a cationic (or positively charged) glass fiber polymer membrane (AHM-GF); and f) The polymer membrane of step e) is treated with a KOH solution to form OH - Doped anion exchange polymer electrolyte membrane (AEPEM) or OH - forming a doped glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF); having The method wherein at least one of the monomers has a quaternary ammonium salt.

2. 2. The method of claim 1 , The method, wherein the reaction solution comprises 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and poly(ethylene glycol) diacrylate (PEGDA).

3. 3. The method of claim 2, The method, wherein the reaction solution comprises 1-1.8 wt % of 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), 4-7.2 wt % of hydroxyethyl methacrylate (HEMA), 1-5 wt % of poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and 1 wt % of poly(ethylene glycol) diacrylate (PEGDA).

4. 4. The method according to any one of claims 1 to 3, The method wherein the reaction solution comprises 1.2-1.6 wt % 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), 5.4-5.8 wt % hydroxyethyl methacrylate (HEMA), 2.8-3.2 wt % poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and 1 wt % poly(ethylene glycol) diacrylate (PEGDA).

5. 2. The method of claim 1 , The method, wherein the monomer / oligomer in step a) is selected from poly(ethylene glycol) based monomers or oligomers, preferably the monomer / polymer is a poly(ethylene glycol) based derivative.

6. 2. The method of claim 1 , A process wherein all steps a) to f), including optional step c), are carried out at a temperature range of 20-30° C. and without the need for a solvent.

7. A battery having an anion exchange polymer electrolyte membrane prepared by the method of any one of claims 1 to 6.

8. a) Pt / C or Pt / C-RuO based on gas diffusion layer substrate or carbon cloth substrate 2 Air cathode or in-situ polymerized Pt / C or Pt / C-RuO 2 Air cathode, b) an anion exchange polymer electrolyte membrane (AEPEM) or a glass fiber anion exchange polymer electrolyte membrane (AEPEM-GF) prepared by the method of claim 1; c) a zinc anode, and d) Metal case A zinc-air battery comprising:

9. 9. The air zinc battery according to claim 8, The metal case has a base, a spacer, and a spring, and is a coin cell type zinc-air battery.

10. 9. The air zinc battery according to claim 8, The membrane has a maximum stretchability of 68-70% and a tensile stress in the range of about 280-290 kPa.

11. 9. The air zinc battery according to claim 8, In-situ polymerization Pt / C-RuO 2 The air cathode is a) brush coating a reaction solution comprising 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and an acrylate / methacrylate monomer / oligomer crosslinker; b) subjecting the polymer-coated air cathode to UV polymerization to obtain an AHM coating on the cathode surface; and c) converting the AHM coating into an AEPEM coating or an AEPEM-GF coating by contacting the AHM polymer coating with a KOH solution of the AEPEM-GF membrane during battery construction; A zinc-air battery prepared by the method described above.

12. 9. The air zinc battery according to claim 8, In-situ polymerized Pt / C or Pt / C-RuO 2 The AEPEM-GF composite electrolyte membrane in combination with an air cathode improves the electrode-electrolyte contact in a zinc-air battery.

13. 9. The air zinc battery according to claim 8, a) an anode made of a thin zinc foil with a thickness of 0.1 mm; b) Pt / C or Pt / C-RuO with a thin layer of polymer coating polymerized in-situ from a precursor solution containing 2-[(acryloyloxy)ethyl]trimethylammonium chloride solution (AOETMA), hydroxyethyl methacrylate (HEMA), poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), and acrylate / methacrylate monomer / oligomer crosslinker. 2 a cathode having a coated gas diffusion layer substrate or a carbon cloth substrate; and c) AEPEM or AEPEM-GF membrane as quasi-solid electrolyte having An air-zinc battery in which the AEPEM or AEPEM-GF membrane is sandwiched between a catalyst-coated carbon cloth or gas diffusion layer substrate and zinc foil.